Mixed phase bioceramics in the CaMgSi2O6 – MoO3 system: Mechanical properties and in-vitro bioactivity. Issue 23 (1st December 2021) - Chen, Wen-Fan; Tseng, Yu-Sheng; Chang, Yu-Man; Zhang, Ji; Su, Yun-Han; Wen, Zhi-Hong; Henry Hanaor, Dorian Amir; Hsu, Wen-Hsin; Pan, Cheng-Tang
Abstract: Mixed phase materials in the quasi binary diopside (CaMgSi2 O6 ) – molybdite (MoO3 ) system were synthesized by a precipitation method. Materials were fabricated with diopside to molybdite ratios of 1:0, 10:1, 5:1, 2:1 and 1:1. XRD, SEM and EDS results show that alongside the initial diopside phase, phases such as calcium molybdate CaMoO4, rod-like enstatite MgSiO3 and cristobalite SiO2 formed as the molybdite content increased, and diopside was entirely absent at the highest molybdite content. At lower Mo content, mixed phase materials showed higher hardness and slower biodegradation in SBF relative to pristine diopside, while maintaining reasonable hydroxyapatite (HAp) formation capability. In contrast, materials with higher molybdite content exhibited lower hardness and bioactivity. The variation in the mechanical and bioactive performance could be attributed to the presence of bulk CaMoO4, acting as a reinforcement, and rod-like MgSiO3 with a highly porous and fragile structure. The trend of hardness is not consistent to the proportion of the component phases could be attributed to morphologies, interfaces, and densities of the samples. Both of secondary phases had poorer HAp deposition compared to pure diopside, indicating the MoO3 addition lowered mixed phase CaMgSi2 O6 – MoO3 bioceramics' ability to form Hap. The results suggest that moderate addition of molybdite to diopside would be an effective pathway towards crystalline bioceramics with enhanced performance.